Towards Physical Descriptors of Active and Selective Catalysts for the Oxidation of n‐Butane to Maleic Anhydride. Issue 8 (14th May 2013) - Eichelbaum, Maik; Glaum, Robert; Hävecker, Michael; Wittich, Knut; Heine, Christian; Schwarz, Heiner; Dobner, Cornelia‐Katharina; Welker‐Nieuwoudt, Cathrin; Trunschke, Annette; Schlögl, Robert
Abstract Based on our newly developed microwave cavity perturbation technique, the microwave conductivity of diverse vanadium(III), (IV), and (V) phosphate catalysts was measured under reaction conditions for the selective oxidation of n‐butane. The conductivity response on the gas phase was identified as a very sensitive measure for the redox kinetics, reversibility, and stability of the samples, which are important prerequisites for highly selective and active catalysts. The sensitivity achieved by our method was comparable to surface‐sensitive methods such as X‐ray photoelectron spectroscopy, whereas more conventional analytic techniques such as X‐ray diffractometry or Raman spectroscopy only indicated the stability of the bulk crystal phase under the same reaction conditions.